Clinicopathological, microenvironmental and genetic determinants of molecular subtypes in KEAP1/NRF2‐mutant lung cancer. Issue 4 (4th December 2018) - Cai, Mei‐Chun; Chen, Minjiang; Ma, Pengfei; Wu, Jie; Lu, Haijiao; Zhang, Shengzhe; Liu, Jin; Zhao, Xiaojing; Zhuang, Guanglei; Yu, Zhuang; Fu, Yujie
Abstract : Somatic KEAP1‐NRF2 pathway alterations are frequently detected in both lung adenocarcinomas and squamous cell carcinomas. However, the biological characteristics and molecular subtypes of KEAP1/NRF2‐mutant lung cancer remain largely undefined. Here, we performed a stepwise, integrative analytic and experimental interrogation of primary tumors and cancer cell lines harboring KEAP1 or NFE2L2 (encoding NRF2) gene mutations. First, we discovered that KEAP1/NRF2‐mutant lung cancer presented APOBEC‐mediated mutational signatures, impaired tumor angiogenesis, elevated hypoxic stress and deficient immune‐cell infiltrates. Second, gene expression‐based subtyping revealed three molecular subsets of KEAP1/NRF2‐mutant lung adenocarcinomas and two molecular subsets of KEAP1/NRF2‐mutant lung squamous cell carcinomas, each associated with distinguishing genetic, differentiation, immunological and clinicopathological properties. Third, single‐sample prediction allowed for de novo identification of KEAP1/NRF2‐active tumors within KEAP1/NRF2‐wild‐type samples. Our data demonstrate that KEAP1/NRF2‐mutant lung cancer is a microenvironmentally distinct, biologically heterogeneous, and clinically underestimated disease. These new pathological and molecular insights may accelerate the development of efficacious therapeutic strategies against human malignancies featured by KEAP1‐NRF2 pathway activation. Abstract : What's new? The stress‐sensor KEAP1 and transcription factor NRF2 serve a key cooperative role in cytoprotection against oxidative stress. In lung cancer, these proteins frequently are mutated, though the functional consequences remain unknown. Here, comprehensive analysis of primary lung tumors harboring genetic mutations in KEAP1 or the NRF2‐encoding gene NFE2L2 identifies KEAP1/NRF2‐mutant lung cancer as a pathologically distinct disease. Moreover, tumors exhibited unique mutation profiles, which were differentiated into transcriptional subtypes and associated with diverse disease patterns. The data suggest that KEAP1/NRF2‐mutant lung cancer is a clinically relevant disease, warranting further investigation into possible avenues for targeted therapeutic intervention.